KHAZANAH ARSIP PARIWISATA KOLONIAL DI INDONESIA: Array - Achmad Sunjayadi (Arsip Nasional Republik Indonesia, 2019)
In doing research of Indonesian historiography in the colonial period, primary sources in the form of colonial archives are important. That includes historiography of tourism in Indonesia. This article describes archival collection of the National Archives of Indonesia related to tourism in the colonial period of Indonesia and attempts to determine the related keywords. The results are information about the tourism activities was the history of the institution, namely Vereeniging Toeristenverkeer and the keywords that used, were 'Vereeniging toeristenverkeer' and 'toerisme'. The archival sources are mainly from the collection of Algemene Secretarie. There are many other collections, it is possible, considering that tourism activities are not only the concern of single institution. Tourism activities are also includes tourist attractions, infrastructure, transportation, accommodation and security.